Enhancing the Understanding of Perceptual-Motor Skills through Video Notational Analysis : A Video Notational Analysis of Visual Exploration, Team Communication, and Creativity in Elite Soccer - Caso, S. (Netherlands Aerospace Centre NLR, 2025)
This doctoral thesis investigates the perceptual-motor skills essential for elite soccer performance, with a focus on creativity, variability in actions, visual exploratory activity (VEA), and intra-team communication. Using video notational analysis, a method that bridges the gap between controlled laboratory studies and the complex and dynamic conditions of competitive sport, this thesis examines how these skills manifest and influence performance. The studies are grounded in the ecological psychology framework, which emphasizes the continuous interaction between perception and action within the sporting environment. The thesis comprises five studies. The first study explores how small-sided games encourage creative actions, proposing that increased action variability fosters creativity. The second and third studies examine the VEA rates (considering the number of VEA in the time frame prior to ball possession) of elite soccer players, comparing different field positions and distinguishing between super-elite (award-winning) players and their elite teammates. The findings highlight how VEA, defined as purposeful body or head movements to gather environmental information, correlates with successful passing outcomes. The fourth and fifth studies focus on intra-team communication. A case study assesses the effectiveness of traditional video notational analysis compared to methods incorporating audio recordings, allowing for a more comprehensive examination of verbal and nonverbal communication. The final study challenges static, cognitive models of communication in sport, instead proposing an ecological perspective in which communication dynamically facilitates collective attention and shared affordances among teammates. This thesis contributes to a deeper understanding of how perceptual-motor skills can be analyzed, trained, and applied to enhance elite soccer performance. It advocates for methodologies that preserve ecological validity, ensuring that research findings remain relevant to real-world sporting contexts.
CC BY-ND 4.0